Successful Regulatory T Cell-Based Therapy Relies on Inhibition of T Cell Effector Function and Enrichment of FOXP3+ Cells in a Humanized Mouse Model of Skin Inflammation - S. Landman; V. L. de Oliveira; M. Peppelman; E. Fasse; E. van Rijssen; S. C. Bauland; P. van Erp; I. Joosten; H. J. P. M. Koenen (Journal of Immunology Research)
Background. Recent clinical trials using regulatory T cells (Treg) support the therapeutic potential of Treg-based therapy in transplantation and autoinflammatory diseases. Despite these clinical successes, the effect of Treg on inflamed tissues, as well as their impact on immune effector function in vivo, is poorly understood. Therefore, we here evaluated the effect of human Treg injection on cutaneous inflammatory processes in vivo using a humanized mouse model of human skin inflammation (huPBL-SCID-huSkin). Methods. SCID beige mice were transplanted with human skin followed by intraperitoneal (IP) injection of 20‐40×106 allogeneic human PBMCs. This typically results in human skin inflammation as indicated by epidermal thickening (hyperkeratosis) and changes in dermal inflammatory markers such as the antimicrobial peptide hBD2 and epidermal barrier cytokeratins K10 and K16, as well as T cell infiltration in the dermis. Ex vivo-expanded human Treg were infused intraperitoneally. Human cutaneous inflammation and systemic immune responses were analysed by immunohistochemistry and flow cytometry. Results. We confirmed that human Treg injection inhibits skin inflammation and the influx of effector T cells. As a novel finding, we demonstrate that human Treg injection led to a reduction of IL-17-secreting cells while promoting a relative increase in immunosuppressive FOXP3+ Treg in the human skin, indicating active immune regulation in controlling the local proinflammatory response. Consistent with the local control (skin), systemically (splenocytes), we observed that Treg injection led to lower frequencies of IFNγ and IL-17A-expressing human T cells, while a trend towards enrichment of FOXP3+ Treg was observed. Conclusion. Taken together, we demonstrate that inhibition of skin inflammation by Treg infusion, next to a reduction of infiltrating effector T cells, is mediated by restoring both the local and systemic balance between cytokine-producing effector T cells and immunoregulatory T cells. This work furthers our understanding of Treg-based immunotherapy.